L’institutionnalisme méthodologique d’Elinor Ostrom : quelques enjeux et controverses - Jean-Pierre Chanteau; Agnès Labrousse (Revue de la Régulation)
This paper explores an underestimated part of Ostrom’s contribution: her methodological institutionalism, beyond her well-known work on the commons. We show that her approach is in line with historical institutionalism (bounded rationality and social embeddedness; role of rules and norms; generative and non-functionalist approach; multi-level and structural analysis; critical realism, etc.), even when she uses models often branded as mainstream (game theory, agent-based models) for heuristic purposes. We thereby unravel recurring misunderstandings in the French literature on Ostrom’s work (about her alleged theory of a “third way”; about the notions of ‘self-governance’ and ‘community’) and point to the potential fruitfulness of a mutual enrichment with other institutionalisms.